2021 43rd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2021
DOI: 10.1109/embc46164.2021.9630954
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the hCoV-19 Informational Architecture

Abstract: The hCoV-19 virus is continuously evolving to highly infectious and lethal variants. There is a latent risk that current vaccines will not be effective over these novel variants. This entails comprehending the genome-wide viral information to unveil mutagenic mechanisms of hCoV-19. To date, this virus is studied as a collection of non-related variants, making it challenging to forecast hotspots and their upcoming effects. In this work, we explore genome-wide information to disentangle informational mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…When COVID strike presented an opportunity to explore not only family lexicon divergence but also mutational phenomena, we replicated the previous approach to hCoV-19 virus sequences (Aguilar-Valdez et al, 2021). We confirmed that k-mer sets-or informational compartments-can be linked to particular taxa.…”
Section: The Non-genocentric Search For Minimal Genomesupporting
confidence: 74%
“…When COVID strike presented an opportunity to explore not only family lexicon divergence but also mutational phenomena, we replicated the previous approach to hCoV-19 virus sequences (Aguilar-Valdez et al, 2021). We confirmed that k-mer sets-or informational compartments-can be linked to particular taxa.…”
Section: The Non-genocentric Search For Minimal Genomesupporting
confidence: 74%